Functional differentiation of human dental pulp stem cells into neuron-like cells exhibiting electrophysiological activity - B. Pardo-Rodríguez; A. M. Baraibar; I. Manero-Roig; J. Luzuriaga; J. Salvador-Moya; Y. Polo; R. Basanta-Torres; F. Unda; S. Mato; Gaskon Ibarretxe; Jose Ramon Pineda (Stem Cell Research & Therapy)
Abstract Background and aim Human dental pulp stem cells (hDPSCs) constitute a promising alternative for central nervous system (CNS) cell therapy. Unlike other human stem cells, hDPSCs can be differentiated, without genetic modification, to neural cells that secrete neuroprotective factors. However, a better understanding of their real capacity to give rise to functional neurons and integrate into synaptic networks is still needed. For that, ex vivo differentiation protocols must be refined, especially to avoid the use of fetal animal serum. The aim of our study is to improve existing differentiation protocols of hDPSCs into neuron-like cells. Methods We compared the effects of the (1) absence or presence of fetal serum during the initial expansion phase as a step prior to switching cultures to neurodifferentiation media. We (2) improved hDPSC neurodifferentiation by adding retinoic acid (RA) and potassium chloride (KCl) pulses for 21 or 60 days and characterized the results by immunofluorescence, digital morphometric analysis, RT-qPCR and electrophysiology. Results We found that neural markers like Nestin, GFAP, S100β and p75NTR were expressed differently in neurodifferentiated hDPSC cultures depending on the presence or absence of serum during the initial cell expansion phase. In addition, hDPSCs previously grown as spheroids in serum-free medium exhibited in vitro expression of neuronal markers such as doublecortin (DCX), neuronal nuclear antigen (NeuN), Ankyrin-G and MAP2 after neurodifferentiation. Presynaptic vGLUT2, Synapsin-I, and excitatory glutamatergic and inhibitory GABAergic postsynaptic scaffold proteins and receptor subunits were also present in these neurodifferentiated hDPSCs. Treatment with KCl and RA increased the amount of both voltage-gated Na+ and K+ channel subunits in neurodifferentiated hDPSCs at the transcript level. Consistently, these cells displayed voltage-dependent K+ and TTX-sensitive Na+ currents as well as spontaneous electrophysiological activity and repetitive neuronal action potentials with a full baseline potential recovery. Conclusion Our study demonstrates that hDPSCs can be differentiated to neuronal-like cells that display functional excitability and thus evidence the potential of these easily accessible human stem cells for nerve tissue engineering. These results highlight the importance of choosing an appropriate culture protocol to successfully neurodifferentiate hDPSCs.